A multi-level pore molecular sieve for carbon dioxide adsorption separation and a preparation method thereof
Patent Information
- Application Number
- CN202611031496.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-13
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2046-07-13
AI Technical Summary
[0003]然而,传统微孔SSZ-13沸石分子筛在实际应用过程中仍存在一定局限性:其一,其狭窄的微孔孔道限制了CO2分子在材料内部的扩散速率,尤其在含水或复杂气氛条件下易发生孔道堵塞;其二,单一微孔结构导致吸附动力学性能较差,影响整体吸附效率及循环使用稳定性;其三,在较高压力或较低温度下虽具有一定吸附量,但脱附能耗高,材料抗湿性和循环稳定性仍有待提高
1、本发明为了在分子筛内部构造微孔、介孔相互贯通的树状多级孔,加入纳米炭黑并通过纳米炭黑的嵌入占位和热分解来产生介孔结构,炭黑为强疏水性物质,很难在合成分子筛的水相体系内得到纳米级单颗粒状态的分散,所以纳米炭黑的引入,很容易因为炭黑颗粒的团聚而导致分子筛内部形成大孔结构。为了促进纳米炭黑的分散均匀性,本发明先采用预氧化处理,在炭黑表面引入亲水基团,然后借助分散剂C13异丙醇酰胺的分散作用以及高速剪切工艺,将纳米炭黑以纳米级单颗粒的状态分散在水中,接着本发明用含氨基的硅烷偶联剂对纳米炭黑的表面进行改性,改性后的纳米炭黑表面被氨基覆盖,这些氨基和分散剂C13异丙醇酰胺分子中的酰胺基团能够产生较强的氢键作用,在炭黑表面氨基与C13异丙醇酰胺分子之间强氢键作用下,炭黑的纳米级单颗粒分散状态会更加稳定。为进一步促进纳米炭黑与分子筛晶体骨架网络结合的紧密性,本发明在纳米炭黑表面进行氨基改性的基础上,又做了硅铝包覆,硅铝包覆的作用主要有两点:一是炭黑颗粒表面包覆的硅铝,在晶化反应过程中,能够提供硅源和铝源,促进反应体系中的活性物质在炭黑表面原位生成分子筛骨架晶格网络,这样会进一步促进炭黑颗粒在分子筛本体内部的分散均匀性,最终使炭黑颗粒烧蚀后形成的介孔在分子筛晶格网络中得到更为均匀的分布,二来反应体系内加入的二甲基十八烷基-(3-三甲氧基硅丙基)-氯化铵,其亲水端可能更容易吸附硅铝包覆的炭黑颗粒,这二者的吸附可以促进炭黑所形成介孔与二甲基十八烷基-(3-三甲氧基硅丙基)-氯化铵所形成的微孔或极微量介孔之间的连通性,最终促进树状多级孔结构的形成,所以硅铝包覆炭黑能够大幅提升多级孔分子筛的二氧化碳吸附性能;
Smart Images

Figure CN122538071B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a multi-level porous molecular sieve for carbon dioxide adsorption and separation and its preparation method, belonging to the field of adsorption and separation technology. Background Technology
[0002] There are four gases that contribute to global warming: carbon dioxide (CO2), nitrous oxide, methane, and hydrofluorocarbons (HFCs). As a greenhouse gas, excessive CO2 emissions undoubtedly contribute to the greenhouse effect, leading to more frequent extreme weather events and causing environmental problems such as desertification and sea-level rise. To reduce CO2 emissions, carbon capture and storage (CCS) technology has emerged. The International Energy Agency believes that CCS technology can contribute approximately 20% to CO2 emission reductions, and since CCS technology allows for the continued use of fossil fuels, CO2 capture technology has received widespread attention and has developed rapidly. Among various CO2 capture and treatment technologies, adsorption methods are widely studied and applied due to their advantages of mild operating conditions, low energy consumption, and high process flexibility. Adsorption methods mainly rely on adsorbent materials to achieve CO2 adsorption and capture. Common adsorbent materials include low-temperature adsorbents such as molecular sieves, MOFs, and carbon-based adsorbents; medium-temperature adsorbents such as magnesium oxide-based and hydrotalcite-like materials; and high-temperature adsorbents such as lithium-based and calcium oxide-based materials. Molecular sieves, especially zeolite molecular sieves, exhibit good overall performance. Due to their regular pore structure, high specific surface area, and tunable surface properties, they have become an important class of CO2 adsorption materials. Among zeolite molecular sieves, SSZ-13 zeolite, with its eight-membered ring pores (approximately 0.38 nm) and high specific surface area, demonstrates excellent CO2 adsorption capacity and molecular sieving ability, making it particularly suitable for separating CO2 / N2 mixtures.
[0003] However, traditional microporous SSZ-13 zeolite molecular sieves still have certain limitations in practical applications: First, their narrow micropores restrict the diffusion rate of CO2 molecules inside the material, and pore blockage is prone to occur, especially under conditions of water or complex atmospheres; Second, the single microporous structure leads to poor adsorption kinetics, affecting the overall adsorption efficiency and cycle stability; Third, although they have a certain adsorption capacity at higher pressures or lower temperatures, the desorption energy consumption is high, and the material's moisture resistance and cycle stability still need to be improved.
[0004] In recent years, hierarchical porous zeolite materials have shown great promise in catalysis and adsorption due to their combination of the advantages of microporous and mesoporous structures. Introducing mesopores can significantly improve mass transfer efficiency, expose more active sites, and enhance adaptability to larger molecules or complex systems. Although some studies have attempted to apply hierarchical porous structures to zeolites such as Beta and ZSM-5, the construction of hierarchical porous structures in SSZ-13 zeolite is still in its early stages. For example, Chinese patent CN114835133A discloses a method for preparing SSZ-13 molecular sieves with hierarchical porous structures, the resulting products, and their applications. Carbon black is used as an auxiliary agent in the crystallization synthesis reaction. The molar ratios of silicon source, heterogeneous seed crystals, alkali source, organic template agent, carbon black, and water are adjusted, and a segmented dynamic crystallization method is adopted to obtain SSZ-13 molecular sieves with hierarchical porous structures. The resulting molecular sieves have advantages such as facilitating macromolecular diffusion and have broad application prospects in petrochemicals, MTO reactions, fine chemicals, and tail gas catalytic redox reactions. For example, Chinese patent CN112978749A discloses a method for preparing and using hierarchical porous SSZ-13 molecular sieves, as well as a method for methanol-to-olefins conversion. The method involves mixing microporous SSZ-13 molecular sieves, a molecular sieve framework protectant, and water to obtain a framework-protected SSZ-13 molecular sieve. The framework-protected SSZ-13 molecular sieve is then subjected to alkali treatment, acid treatment, ammonium ion exchange, and calcination to obtain a hierarchical porous SSZ-13 molecular sieve. This type of molecular sieve exhibits superior performance in the methanol-to-olefins process, showing high selectivity for ethylene and propylene and a longer reaction lifetime. Neither of these patents addresses the application of hierarchical porous SSZ-13 molecular sieves in CO2 adsorption. Systematic research in this area is not yet fully developed, and attempts at industrial application are almost nonexistent. Therefore, developing an SSZ-13 zeolite material with a hierarchical porous structure to enhance CO2 adsorption capacity, improve adsorption kinetics, and cycle stability has significant scientific value and industrial application potential.
[0005] The present invention aims to overcome the limitations of existing microporous SSZ-13 materials and provide a novel method for preparing multi-level porous SSZ-13 zeolite molecular sieves and its application in CO2 adsorption, so as to meet the higher requirements of carbon capture and separation processes. Summary of the Invention
[0006] To address the shortcomings of the existing technologies, this invention provides a multi-level porous molecular sieve for carbon dioxide adsorption and separation and its preparation method, achieving the following objectives: preparing an SSZ-13 zeolite molecular sieve with a dendritic multi-level porous structure, good pore size distribution, and large carbon dioxide adsorption capacity.
[0007] To achieve the above-mentioned objectives, the present invention adopts the following technical solution: A hierarchical porous molecular sieve for carbon dioxide adsorption and separation and its preparation method are disclosed. The preparation method of the hierarchical porous molecular sieve for carbon dioxide adsorption and separation includes four steps: preparing a silica-alumina coated carbon black pre-dispersion liquid, preparing a precursor solution, preparing hierarchical porous SSZ-13 molecular sieve raw powder, and ion exchange. The following are further improvements to the above technical solution: Step 1: Preparation of silica-alumina coated carbon black pre-dispersion Pre-oxidized carbon black, C13 isopropanol amide, and deionized water were placed in a dispersion vessel and dispersed at high speed until uniform. Then, the dispersion rate was reduced, the temperature was raised to the reaction temperature, and an amino-containing silane coupling agent was added. After the coupling agent reacted completely, an aqueous solution of sodium metasilicate was added, followed by the dropwise addition of an aqueous solution of sulfuric acid. The pH value in the vessel was controlled to remain stable between 9 and 10 during the silicon coating reaction. After the silicon coating reaction was completed, the mixture was aged once. After aging, it was dispersed at high speed again until uniform. Then, the dispersion rate was reduced, and an aqueous solution of aluminum sulfate was added, followed by the dropwise addition of an aqueous solution of sodium hydroxide. The pH value in the vessel was controlled to remain stable between 6 and 6.8 during the aluminum coating reaction. After the aluminum coating reaction was completed, the mixture was aged a second time. After aging, a silicon-aluminum coated carbon black pre-dispersion was obtained. The pre-oxidation treatment involves mixing carbon black with an ammonium persulfate aqueous solution with a mass concentration of 0.5 wt‰ at a mass ratio of 9:100, stirring and oxidizing at room temperature for 24 hours, and then filtering and drying at 100°C for 12 hours to obtain the pre-oxidized carbon black. The particle size of the carbon black is 9~20nm; The amino-containing silane coupling agent is at least one of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, and N-(2-aminoethyl)-3-aminopropyltriethoxysilane. The sodium metasilicate aqueous solution contains 8-13 wt% sodium metasilicate. The sulfuric acid aqueous solution contains 6-10 wt% sulfuric acid. The aluminum sulfate aqueous solution contains 10-20 wt% aluminum sulfate. The sodium hydroxide aqueous solution contains 4-10 wt% sodium hydroxide. The mass ratio of the pre-oxidized carbon black, C13 isopropanol amide, deionized water, amino-containing silane coupling agent, sodium metasilicate aqueous solution, and aluminum sulfate aqueous solution is (35~100):(1~2.5):(390~1500):(0.1~2):(9~30):(11~40). The high-speed dispersion is uniform, with a dispersion rate of 10,000~16,000 rpm and a dispersion time of 5~9 hours; The dispersion rate is reduced to 1500~2600 rpm; The reaction temperature is 60~70℃; After the coupling agent has completely reacted, the reaction time is 2 to 5 hours; The silicon coating reaction takes 2 to 3.5 hours. The aging process, in this first stage, lasts for 2 to 3 hours. The second high-speed dispersion is carried out at a dispersion rate of 10,000 to 16,000 rpm for a dispersion time of 0.5 to 1.5 hours. The aluminum coating reaction takes 1.5 to 3 hours. The secondary aging process takes 2 to 3 hours.
[0008] Step 2: Preparation of precursor solution Sodium hydroxide, N,N,N-trimethyl-1-adamantyl ammonium hydroxide, and deionized water were mixed evenly. Then, silica-alumina coated carbon black pre-dispersion and aluminum isopropoxide were added. After stirring and mixing evenly, the mixture was placed in an ice-water bath. Tetraethyl silicate was added at a constant temperature of 0°C. After stirring and hydrolysis was complete, the mixture was raised to room temperature, stirred thoroughly, and aged to obtain the precursor solution. The molar ratio of tetraethyl silicate, aluminum isopropoxide, sodium hydroxide, and N,N,N-trimethyl-1-adamantyl ammonium hydroxide is as follows: SiO2 : Al2O3 : Na2O : N,N,N-trimethyl-1-adamantyl ammonium hydroxide = 1 : (0.09~0.1) : (0.2~0.24) : (0.2~0.23). The mass of the deionized water added is 1 to 13 times the total mass of tetraethyl silicate, aluminum isopropoxide, sodium hydroxide, and N,N,N-trimethyl-1-adamantyl ammonium hydroxide. The mass of the silica-alumina coated carbon black pre-dispersion is 1 to 10 times the total mass of tetraethyl silicate, aluminum isopropoxide, sodium hydroxide, and N,N,N-trimethyl-1-adamantyl ammonium hydroxide. The mixing process is carried out at a speed of 800-1800 rpm for 1-3 hours until the mixture is homogeneous. The stirring process is complete, with a stirring rate of 1000-2000 rpm and a stirring time of 6-15 minutes. The mixture is brought to room temperature and stirred thoroughly at a stirring rate of 1000-2000 rpm for 1-3 hours. The aging process takes 10 to 40 hours.
[0009] Step 3: Preparation of multi-level porous SSZ-13 molecular sieve raw powder After the precursor solution is evaporated to remove alcohol and pre-crystallized, it is placed in an ice-water bath and slowly added dropwise at 0°C with vigorous stirring. After the addition is complete, vigorous stirring is continued at 0°C until the mixture is homogeneous, and the mixture is then transferred to a hydrothermal reactor. After hydrothermal crystallization, the mixture is centrifuged, washed, dried and calcined to obtain multi-level porous SSZ-13 molecular sieve raw powder. The amount of dimethyloctadecyl-(3-trimethoxysilylpropyl)-ammonium chloride added is 0.03 to 0.05 times the total molar amount of tetraethyl silicate added to the precursor solution; The specific operation of the evaporation to remove alcohol is as follows: the precursor solution is transferred into a rotary evaporator and continuously evaporated for 4 to 10 hours under the conditions of temperature 40 to 80°C, rotation speed 50 to 100 rpm and vacuum degree 50 to 80 kPa. The pre-crystallization temperature is 90~120℃, and the pre-crystallization time is 10~20 hours; The vigorous stirring is carried out at a speed of 1500~3500 rpm; The dimethyloctadecyl-(3-trimethoxysilylpropyl)-ammonium chloride is added dropwise at a rate of 10-120 g / min. The mixture is stirred vigorously until homogeneous, and the stirring and mixing time is 4 to 8 hours. The hydrothermal crystallization is carried out at a temperature of 120~180℃ for 3~10 days. The washing process involves first washing with deionized water until the pH of the washing solution is neutral, and then washing with ethanol 1-2 times, with the mass of ethanol used in each wash being equal to the mass of the wet solid being washed. The drying process is carried out at 80~100℃ for 12~20 hours; The calcination is carried out in an argon or nitrogen atmosphere at 350-400°C for 4-7 hours, followed by calcination in air at 530-580°C for 4-6 hours.
[0010] Step 4, Ion exchange The raw powder of hierarchical SSZ-13 molecular sieve was added to an ammonium chloride aqueous solution and subjected to the first ion exchange under constant temperature stirring. After filtration, washing and drying, the second ion exchange was carried out under the same constant temperature stirring operation. After filtration, washing and drying, the third ion exchange was carried out under the same constant temperature stirring operation. Then, the filtered, washed and dried powder was calcined at 530~580℃ for 4~6 hours to obtain a hierarchical porous molecular sieve for carbon dioxide adsorption and separation. The concentration of the ammonium chloride aqueous solution is 0.8~1 mol / L; In the first, second, and third ion exchanges, the mass ratio of solid powder to ammonium chloride aqueous solution is 1:1 to 3.5 in each ion exchange. Under constant temperature stirring, the constant temperature is 70~90℃ and the stirring speed is 500~1000 rpm; The duration of each of the first, second, and third ion exchanges is 2 to 3.5 hours. The washing process involves washing with deionized water 2-3 times, with the mass of deionized water used each time being equal to the mass of the wet solid being washed. The drying process involves a drying temperature of 90-110℃ and a drying time of 7-12 hours.
[0011] Compared with the prior art, the present invention achieves the following beneficial effects: 1. In order to construct a tree-like hierarchical pore structure with interconnected micropores and mesopores inside the molecular sieve, this invention adds nano-carbon black and generates a mesoporous structure through the embedding and thermal decomposition of nano-carbon black. Carbon black is a strongly hydrophobic substance, and it is difficult to obtain nano-sized single-particle dispersion in the aqueous system for synthesizing molecular sieves. Therefore, the introduction of nano-carbon black can easily lead to the formation of a macroporous structure inside the molecular sieve due to the agglomeration of carbon black particles. To promote the uniform dispersion of nano-carbon black, this invention first employs a pre-oxidation treatment to introduce hydrophilic groups onto the carbon black surface. Then, with the aid of the dispersant C13 isopropanol amide and a high-speed shearing process, the nano-carbon black is dispersed in water as nano-sized single particles. Next, this invention modifies the surface of the nano-carbon black with an amino-containing silane coupling agent. The modified surface of the nano-carbon black is covered with amino groups. These amino groups and the amide groups in the C13 isopropanol amide molecules can generate strong hydrogen bonds. Under the strong hydrogen bond interaction between the amino groups and the C13 isopropanol amide molecules on the carbon black surface, the nano-sized single particle dispersion of the carbon black becomes more stable. To further enhance the tightness of the bond between nano-carbon black and the molecular sieve crystal framework network, this invention, based on amino modification of the nano-carbon black surface, also incorporates a silicon-aluminum coating. The silicon-aluminum coating serves two main purposes: firstly, the silicon and aluminum coating on the carbon black particle surface provides silicon and aluminum sources during the crystallization reaction, promoting the in-situ generation of the molecular sieve framework lattice network on the carbon black surface by the active substances in the reaction system. This further promotes the uniform dispersion of carbon black particles within the molecular sieve body, ultimately enhancing the mesopores formed after the carbon black particles are ablated. The first advantage is that the carbon black particles are more evenly distributed in the lattice network of the molecular sieve. Secondly, the hydrophilic end of the dimethyloctadecyl-(3-trimethoxysilylpropyl)-ammonium chloride added to the reaction system may more easily adsorb the silica-alumina coated carbon black particles. The adsorption of these two can promote the connectivity between the mesopores formed by carbon black and the micropores or trace mesopores formed by dimethyloctadecyl-(3-trimethoxysilylpropyl)-ammonium chloride, and ultimately promote the formation of a dendritic hierarchical pore structure. Therefore, silica-alumina coated carbon black can significantly improve the carbon dioxide adsorption performance of hierarchical porous molecular sieves. 2. This invention introduces two soft templates, N,N,N-trimethyl-1-adamantylammonium hydroxide and dimethyloctadecyl-(3-trimethoxysilylpropyl)-ammonium chloride, to jointly construct micropores. Dimethyloctadecyl-(3-trimethoxysilylpropyl)-ammonium chloride not only assists in the formation of the microporous framework, but its self-assembly behavior and affinity for silica-alumina coated carbon black particles enable it to induce a certain number of micro- and mesoporous interconnected channels while constructing rich micropores inside the molecular sieve crystal. Thus, without sacrificing the crystallinity and thermal stability of the zeolite, effective interconnection between micropores and mesopores is achieved, ultimately resulting in a dendritic hierarchical porous structure with low diffusion resistance and excellent adsorption performance. 3. The main advantages of the dendritic hierarchical porous molecular sieve obtained by the present invention in adsorbing carbon dioxide are: as a high-speed diffusion channel, the mesopores can greatly alleviate the mass transfer limitation of CO2 molecules in the micropore channels, making the internal adsorption sites easier to access. At the same time, the rich pore structure also reduces the risk of pore blockage caused by capillary condensation in the adsorption-desorption cycle, and exhibits particularly excellent adsorption-desorption stability when treating humid flue gas. 4. The hierarchical porous molecular sieve for carbon dioxide adsorption and separation obtained in this invention has a breakthrough time of 628~650s, a dynamic adsorption capacity of 2.55~2.92 mmol / g, and an apparent diffusion coefficient D of (5.2~5.8)×10⁻⁶. - 12 m 2 / s. Attached Figure Description
[0012] Figure 1 The XRD patterns of the hierarchical porous molecular sieves used for carbon dioxide adsorption and separation obtained in Example 1, Comparative Example 3, and Comparative Example 4 are shown. Figure 2 The nitrogen adsorption-desorption curves of the hierarchical porous molecular sieves used for carbon dioxide adsorption and separation obtained in Examples 1, 3, and 4 are shown. Detailed Implementation
[0013] The preferred embodiments of the present invention are described below. It should be understood that the preferred embodiments described herein are for illustration and explanation only and are not intended to limit the present invention.
[0014] Example 1: A method for preparing a hierarchical porous molecular sieve for carbon dioxide adsorption and separation Step 1: Preparation of silica-alumina coated carbon black pre-dispersion Pre-oxidized carbon black, C13 isopropanol amide, and deionized water were placed in a dispersion vessel and dispersed at high speed until uniform. Then, the dispersion rate was reduced, the temperature was raised to the reaction temperature, and an amino-containing silane coupling agent was added. After the coupling agent reacted completely, an aqueous solution of sodium metasilicate was added, followed by the dropwise addition of an aqueous solution of sulfuric acid. The pH value in the vessel was kept stable at 9.8 during the silicon coating reaction. After the silicon coating reaction was completed, the mixture was aged once. After aging, it was dispersed at high speed again until uniform. Then, the dispersion rate was reduced, and an aqueous solution of aluminum sulfate was added. Then, an aqueous solution of sodium hydroxide was added, followed by the dropwise addition of an aqueous solution of sodium hydroxide. The pH value in the vessel was kept stable at 6.5 during the aluminum coating reaction. After the aluminum coating reaction was completed, the mixture was aged a second time. After aging, a silicon-aluminum coated carbon black pre-dispersion was obtained. The pre-oxidation treatment involves mixing carbon black with an ammonium persulfate aqueous solution with a mass concentration of 0.5 wt‰ at a mass ratio of 9:100, stirring and oxidizing at room temperature for 24 hours, and then filtering and drying at 100°C for 12 hours to obtain the pre-oxidized carbon black. The carbon black has a particle size of 13 nm; The amino-containing silane coupling agent is N-(2-aminoethyl)-3-aminopropyltrimethoxysilane; The sodium metasilicate aqueous solution contained 11 wt% sodium metasilicate. The sulfuric acid in the sulfuric acid aqueous solution has a sulfuric acid mass fraction of 9 wt%. The aluminum sulfate aqueous solution contained 14 wt% aluminum sulfate. The sodium hydroxide aqueous solution has a sodium hydroxide mass fraction of 8 wt%. The mass ratio of the pre-oxidized carbon black, C13 isopropanol amide, deionized water, amino-containing silane coupling agent, sodium metasilicate aqueous solution, and aluminum sulfate aqueous solution is 65:2:1100:1:15:25. The high-speed dispersion is uniform, with a dispersion rate of 13,000 rpm and a dispersion time of 8 hours; The dispersion rate is reduced to 2000 rpm; The reaction temperature is 66°C; The reaction time after the coupling agent has completely reacted is 4 hours; The silicon coating reaction takes 3 hours. The aging process, in this case, lasts for 2.6 hours. The second high-speed dispersion was carried out at a dispersion rate of 13,000 rpm for 1 hour. The aluminum coating reaction takes 2 hours. The secondary aging process takes 2.6 hours.
[0015] Step 2: Preparation of precursor solution Sodium hydroxide, N,N,N-trimethyl-1-adamantyl ammonium hydroxide, and deionized water were mixed evenly. Then, silica-alumina coated carbon black pre-dispersion and aluminum isopropoxide were added. After stirring and mixing evenly, the mixture was placed in an ice-water bath. Tetraethyl silicate was added at a constant temperature of 0°C. After stirring and hydrolysis was complete, the mixture was raised to room temperature, stirred thoroughly, and aged to obtain the precursor solution. The molar ratio of tetraethyl silicate, aluminum isopropoxide, sodium hydroxide, and N,N,N-trimethyl-1-adamantyl ammonium hydroxide is 1:0.095:0.22:0.21. The added deionized water is 4 times the total mass of tetraethyl silicate, aluminum isopropoxide, sodium hydroxide, and N,N,N-trimethyl-1-adamantyl ammonium hydroxide. The mass of the silica-alumina coated carbon black predispersant added is twice the total mass of tetraethyl silicate, aluminum isopropoxide, sodium hydroxide, and N,N,N-trimethyl-1-adamantyl ammonium hydroxide. The mixture is stirred until homogeneous, at a stirring speed of 1500 rpm, for a stirring time of 2 hours; The stirring hydrolysis was complete at a stirring rate of 1200 rpm for 10 minutes. The mixture was brought to room temperature and thoroughly stirred at a stirring rate of 1300 rpm for 2 hours. The aging process takes 20 hours.
[0016] Step 3: Preparation of multi-level porous SSZ-13 molecular sieve raw powder After the precursor solution is evaporated to remove alcohol and pre-crystallized, it is placed in an ice-water bath and slowly added dropwise at 0°C with vigorous stirring. After the addition is complete, vigorous stirring is continued at 0°C until the mixture is homogeneous, and the mixture is then transferred to a hydrothermal reactor. After hydrothermal crystallization, the mixture is centrifuged, washed, dried and calcined to obtain multi-level porous SSZ-13 molecular sieve raw powder. The amount of dimethyloctadecyl-(3-trimethoxysilylpropyl)-ammonium chloride added is 0.04 times the total molar amount of tetraethyl silicate added to the precursor solution; The specific operation of the evaporation to remove alcohol is as follows: the precursor solution is transferred into a rotary evaporator and continuously evaporated for 8 hours at a temperature of 60°C, a rotation speed of 80 rpm, and a vacuum of 70 kPa. The pre-crystallization temperature is 110℃ and the pre-crystallization time is 18 hours. The vigorous stirring was carried out at a stirring rate of 2600 rpm. The dimethyloctadecyl-(3-trimethoxysilylpropyl)-ammonium chloride was added dropwise at a rate of 80 g / min. The mixture is stirred vigorously until homogeneous, and the stirring and mixing time is 5 hours. The hydrothermal crystallization process is carried out at a temperature of 140°C for 7 days. The washing process involves first washing with deionized water until the pH of the washing solution is neutral, and then washing once with ethanol. The mass of ethanol used for washing is equal to the mass of the wet solid being washed. The drying process involves drying at 95°C for 17 hours. The calcination is carried out in a nitrogen atmosphere at 380°C for 5 hours, followed by calcination in air at 550°C for 5 hours.
[0017] Step 4, Ion exchange The raw powder of multi-level porous SSZ-13 molecular sieve was added to an ammonium chloride aqueous solution and subjected to the first ion exchange under constant temperature stirring. After filtration, washing and drying, the second ion exchange was carried out under the same constant temperature stirring operation. After filtration, washing and drying, the third ion exchange was carried out under the same constant temperature stirring operation. Then, the filtered, washed and dried powder was calcined at 550℃ for 5 hours to obtain a multi-level porous molecular sieve for carbon dioxide adsorption and separation. The concentration of the ammonium chloride aqueous solution is 0.9 mol / L; In the first, second, and third ion exchanges, the mass ratio of solid powder to ammonium chloride aqueous solution is 1:2 in each ion exchange. The constant temperature stirring is 80℃, and the stirring speed is 800 rpm. The first, second, and third ion exchanges each lasted for 3 hours. The washing process involves washing twice with deionized water, with the mass of deionized water used each time being equal to the mass of the wet solid being washed. The drying process involves a drying temperature of 100°C and a drying time of 10 hours.
[0018] Example 2: A method for preparing a hierarchical porous molecular sieve for carbon dioxide adsorption and separation Step 1: Preparation of silica-alumina coated carbon black pre-dispersion Pre-oxidized carbon black, C13 isopropanol amide, and deionized water were placed in a dispersion vessel and dispersed at high speed until uniform. Then, the dispersion rate was reduced and the temperature was raised to the reaction temperature. An amino-containing silane coupling agent was then added. After the coupling agent reacted completely, an aqueous solution of sodium metasilicate was added, followed by the dropwise addition of an aqueous solution of sulfuric acid. The pH value in the vessel was kept stable at 9 during the silicon coating reaction. After the silicon coating reaction was completed, the mixture was aged once. After aging, it was dispersed at high speed again until uniform. Then, the dispersion rate was reduced and an aqueous solution of aluminum sulfate was added. Then, an aqueous solution of sodium hydroxide was added, followed by the dropwise addition of an aqueous solution of sodium hydroxide. The pH value in the vessel was kept stable at 6 during the aluminum coating reaction. After the aluminum coating reaction was completed, the mixture was aged a second time. After aging, a silicon-aluminum coated carbon black pre-dispersion was obtained. The pre-oxidation treatment involves mixing carbon black with an ammonium persulfate aqueous solution with a mass concentration of 0.5 wt‰ at a mass ratio of 9:100, stirring and oxidizing at room temperature for 24 hours, and then filtering and drying at 100°C for 12 hours to obtain the pre-oxidized carbon black. The carbon black has a particle size of 9 nm; The amino-containing silane coupling agent is N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane; The sodium metasilicate aqueous solution contains 8 wt% sodium metasilicate. The sulfuric acid in the sulfuric acid aqueous solution has a sulfuric acid mass fraction of 6 wt%. The aluminum sulfate aqueous solution contains 10 wt% aluminum sulfate. The sodium hydroxide aqueous solution has a sodium hydroxide mass fraction of 4 wt%. The mass ratio of the pre-oxidized carbon black, C13 isopropanol amide, deionized water, amino-containing silane coupling agent, sodium metasilicate aqueous solution, and aluminum sulfate aqueous solution is 35:1:390:0.1:9:11. The high-speed dispersion is uniform, with a dispersion rate of 10,000 rpm and a dispersion time of 9 hours; The dispersion rate is reduced to 1500 rpm; The reaction temperature is 60°C; The reaction time after the coupling agent has completely reacted is 2 hours; The silicon coating reaction takes 2 hours. The aging process, in this first stage, lasts for 2 hours. The second high-speed dispersion is carried out at a dispersion rate of 10,000 rpm for 1.5 hours. The aluminum coating reaction takes 1.5 hours. The secondary aging process takes 2 hours.
[0019] Step 2: Preparation of precursor solution Sodium hydroxide, N,N,N-trimethyl-1-adamantyl ammonium hydroxide, and deionized water were mixed evenly. Then, silica-alumina coated carbon black pre-dispersion and aluminum isopropoxide were added. After stirring and mixing evenly, the mixture was placed in an ice-water bath. Tetraethyl silicate was added at a constant temperature of 0°C. After stirring and hydrolysis was complete, the mixture was raised to room temperature, stirred thoroughly, and aged to obtain the precursor solution. The molar ratio of tetraethyl silicate, aluminum isopropoxide, sodium hydroxide, and N,N,N-trimethyl-1-adamantyl ammonium hydroxide is 1:0.09:0.2:0.2. The added deionized water is 1 times the total mass of tetraethyl silicate, aluminum isopropoxide, sodium hydroxide, and N,N,N-trimethyl-1-adamantyl ammonium hydroxide. The mass of the silica-alumina coated carbon black pre-dispersion added is 1 times the total mass of tetraethyl silicate, aluminum isopropoxide, sodium hydroxide, and N,N,N-trimethyl-1-adamantyl ammonium hydroxide. The mixture is stirred until homogeneous, at a stirring speed of 800 rpm, for a stirring time of 3 hours; The stirring hydrolysis was complete, the stirring rate was 1000 rpm, and the stirring hydrolysis time was 15 minutes; The mixture was brought to room temperature and thoroughly stirred at a stirring rate of 1000 rpm for 3 hours. The aging process lasts for 10 hours.
[0020] Step 3: Preparation of multi-level porous SSZ-13 molecular sieve raw powder After the precursor solution is evaporated to remove alcohol and pre-crystallized, it is placed in an ice-water bath and slowly added dropwise at 0°C with vigorous stirring. After the addition is complete, vigorous stirring is continued at 0°C until the mixture is homogeneous, and the mixture is then transferred to a hydrothermal reactor. After hydrothermal crystallization, the mixture is centrifuged, washed, dried and calcined to obtain multi-level porous SSZ-13 molecular sieve raw powder. The amount of dimethyloctadecyl-(3-trimethoxysilylpropyl)-ammonium chloride added is 0.03 times the total molar amount of tetraethyl silicate added to the precursor solution; The specific operation of the evaporation to remove alcohol is as follows: the precursor solution is transferred into a rotary evaporator and continuously evaporated for 10 hours at a temperature of 40°C, a rotation speed of 100 rpm, and a vacuum of 80 kPa. The pre-crystallization temperature is 90°C and the pre-crystallization time is 20 hours. The vigorous stirring was carried out at a stirring rate of 1500 rpm. The dimethyloctadecyl-(3-trimethoxysilylpropyl)-ammonium chloride was added at a rate of 10 g / min. The mixture is stirred vigorously until homogeneous, and the stirring and mixing time is 4 hours. The hydrothermal crystallization process is carried out at a temperature of 120°C for 10 days. The washing process involves first washing with deionized water until the pH of the washing solution is neutral, and then washing twice with ethanol. The mass of ethanol used in each wash is equal to the mass of the wet solid being washed. The drying process involves drying at 80°C for 20 hours. The calcination process involves calcining at 350°C in a nitrogen atmosphere for 7 hours, followed by calcination at 530°C in air for 6 hours.
[0021] Step 4, Ion exchange The raw powder of hierarchical SSZ-13 molecular sieve was added to an ammonium chloride aqueous solution and subjected to the first ion exchange under constant temperature stirring. After filtration, washing and drying, the second ion exchange was carried out under the same constant temperature stirring operation. After filtration, washing and drying, the third ion exchange was carried out under the same constant temperature stirring operation. Then, the filtered, washed and dried powder was calcined at 530℃ for 6 hours to obtain a hierarchical porous molecular sieve for carbon dioxide adsorption and separation. The concentration of the ammonium chloride aqueous solution is 0.8 mol / L; In the first, second, and third ion exchanges, the mass ratio of solid powder to ammonium chloride aqueous solution is 1:1 in each ion exchange. The constant temperature stirring is 70℃, and the stirring speed is 1000 rpm. The first, second, and third ion exchanges each lasted for 2 hours. The washing process involves washing twice with deionized water, with the mass of deionized water used each time being equal to the mass of the wet solid being washed. The drying process involves a drying temperature of 90°C and a drying time of 12 hours.
[0022] Example 3: A method for preparing a hierarchical porous molecular sieve for carbon dioxide adsorption and separation Step 1: Preparation of silica-alumina coated carbon black pre-dispersion Pre-oxidized carbon black, C13 isopropanol amide, and deionized water were placed in a dispersion vessel and dispersed at high speed until uniform. Then, the dispersion rate was reduced, the temperature was raised to the reaction temperature, and an amino-containing silane coupling agent was added. After the coupling agent reacted completely, an aqueous solution of sodium metasilicate was added, followed by the dropwise addition of an aqueous solution of sulfuric acid. The pH value in the vessel was kept stable at 10 during the silicon coating reaction. After the silicon coating reaction was completed, the mixture was aged once. After aging, it was dispersed at high speed again until uniform. Then, the dispersion rate was reduced, and an aqueous solution of aluminum sulfate was added. Then, an aqueous solution of sodium hydroxide was added, followed by the dropwise addition of an aqueous solution of sodium hydroxide. The pH value in the vessel was kept stable at 6.8 during the aluminum coating reaction. After the aluminum coating reaction was completed, the mixture was aged a second time. After aging, a silicon-aluminum coated carbon black pre-dispersion was obtained. The pre-oxidation treatment involves mixing carbon black with an ammonium persulfate aqueous solution with a mass concentration of 0.5 wt‰ at a mass ratio of 9:100, stirring and oxidizing at room temperature for 24 hours, and then filtering and drying at 100°C for 12 hours to obtain the pre-oxidized carbon black. The carbon black has a particle size of 20 nm; The amino-containing silane coupling agent is N-(2-aminoethyl)-3-aminopropyltriethoxysilane; The sodium metasilicate aqueous solution contains 13 wt% sodium metasilicate. The sulfuric acid in the sulfuric acid aqueous solution has a sulfuric acid mass fraction of 10 wt%. The aluminum sulfate aqueous solution contained 20 wt% aluminum sulfate. The sodium hydroxide aqueous solution has a sodium hydroxide mass fraction of 10 wt%. The mass ratio of the pre-oxidized carbon black, C13 isopropanol amide, deionized water, amino-containing silane coupling agent, sodium metasilicate aqueous solution, and aluminum sulfate aqueous solution is 100:2.5:1500:2:30:40. The high-speed dispersion is uniform, with a dispersion rate of 16,000 rpm and a dispersion time of 5 hours; The dispersion rate is reduced to 2600 rpm; The reaction temperature is 70°C; The reaction time after the coupling agent has completely reacted is 5 hours; The silicon coating reaction takes 3.5 hours. The aging process, in this first stage, lasts for 3 hours. The second high-speed dispersion was carried out at a dispersion rate of 16,000 rpm for 0.5 hours. The aluminum coating reaction takes 3 hours. The secondary aging process takes 3 hours.
[0023] Step 2: Preparation of precursor solution Sodium hydroxide, N,N,N-trimethyl-1-adamantyl ammonium hydroxide, and deionized water were mixed evenly. Then, silica-alumina coated carbon black pre-dispersion and aluminum isopropoxide were added. After stirring and mixing evenly, the mixture was placed in an ice-water bath. Tetraethyl silicate was added at a constant temperature of 0°C. After stirring and hydrolysis was complete, the mixture was raised to room temperature, stirred thoroughly, and aged to obtain the precursor solution. The molar ratio of tetraethyl silicate, aluminum isopropoxide, sodium hydroxide, and N,N,N-trimethyl-1-adamantyl ammonium hydroxide is 1:0.1:0.24:0.23. The added deionized water is 10 times the total mass of tetraethyl silicate, aluminum isopropoxide, sodium hydroxide, and N,N,N-trimethyl-1-adamantyl ammonium hydroxide. The mass of the silica-alumina coated carbon black predispersant added is 3 times the total mass of tetraethyl silicate, aluminum isopropoxide, sodium hydroxide, and N,N,N-trimethyl-1-adamantyl ammonium hydroxide. The mixture is stirred until homogeneous, at a stirring speed of 1800 rpm, for a stirring time of 1 hour; The stirring hydrolysis was complete at a stirring rate of 2000 rpm for 6 minutes. The mixture was brought to room temperature and thoroughly stirred at a stirring rate of 2000 rpm for 1 hour. The aging process takes 40 hours.
[0024] Step 3: Preparation of multi-level porous SSZ-13 molecular sieve raw powder After the precursor solution is evaporated to remove alcohol and pre-crystallized, it is placed in an ice-water bath and slowly added dropwise at 0°C with vigorous stirring. After the addition is complete, vigorous stirring is continued at 0°C until the mixture is homogeneous, and the mixture is then transferred to a hydrothermal reactor. After hydrothermal crystallization, the mixture is centrifuged, washed, dried and calcined to obtain multi-level porous SSZ-13 molecular sieve raw powder. The amount of dimethyloctadecyl-(3-trimethoxysilylpropyl)-ammonium chloride added is 0.05 times the total molar amount of tetraethyl silicate added to the precursor solution; The specific operation of the evaporation to remove alcohol is as follows: the precursor solution is transferred into a rotary evaporator and continuously evaporated for 4 hours at a temperature of 80°C, a rotation speed of 50 rpm, and a vacuum of 50 kPa. The pre-crystallization temperature is 120°C and the pre-crystallization time is 10 hours. The vigorous stirring was carried out at a stirring rate of 3500 rpm. The dimethyloctadecyl-(3-trimethoxysilylpropyl)-ammonium chloride was added at a rate of 120 g / min. The mixture is stirred vigorously until homogeneous, and the stirring and mixing time is 8 hours. The hydrothermal crystallization process is carried out at a temperature of 180°C for 3 days. The washing process involves first washing with deionized water until the pH of the washing solution is neutral, and then washing twice with ethanol. The mass of ethanol used in each wash is equal to the mass of the wet solid being washed. The drying process involves drying at 100°C for 12 hours. The calcination is carried out in an argon atmosphere at 400°C for 4 hours, followed by calcination in air at 580°C for 4 hours.
[0025] Step 4, Ion exchange The raw powder of hierarchical SSZ-13 molecular sieve was added to an ammonium chloride aqueous solution and subjected to the first ion exchange under constant temperature stirring. After filtration, washing and drying, the second ion exchange was carried out under the same constant temperature stirring operation. After filtration, washing and drying, the third ion exchange was carried out under the same constant temperature stirring operation. Then, the filtered, washed and dried powder was calcined at 580℃ for 4 hours to obtain a hierarchical porous molecular sieve for carbon dioxide adsorption and separation. The concentration of the ammonium chloride aqueous solution is 1 mol / L; In the first, second, and third ion exchanges, the mass ratio of solid powder to ammonium chloride aqueous solution is 1:3.5 in each ion exchange. The constant temperature stirring is 90℃, and the stirring speed is 500 rpm. The first, second, and third ion exchanges each lasted 3.5 hours. The washing process involves washing three times with deionized water, with the mass of deionized water used each time being equal to the mass of the wet solid being washed. The drying process is carried out at a temperature of 110°C for 7 hours.
[0026] Comparative Example 1: Based on Example 1, in step 1, preparing the silica-alumina coated carbon black pre-dispersion, C13 isopropanolamide was not added. Instead, 2 parts of C13 isopropanolamide were replaced with 2 parts of deionized water in equal amounts. The specific operation is as follows: Step 1: Preparation of silica-alumina coated carbon black pre-dispersion Based on Example 1, replace 2 parts of C13 isopropanol amide with 2 parts of deionized water in equal amounts, and perform the other operations as in Example 1; Steps 2, 3, and 4 are the same as in Example 1.
[0027] Comparative Example 2: Based on Example 1, in step 1, the preparation of the silica-alumina coated carbon black pre-dispersion solution was not performed with silica-alumina coating. In step 1, only the silane coupling agent modified carbon black pre-dispersion solution was prepared. 15 parts of sodium metasilicate aqueous solution and 25 parts of aluminum sulfate aqueous solution were approximately replaced with 35 parts of deionized water according to their respective deionized water content. The specific operation is as follows: Step 1: Preparation of silane coupling agent modified carbon black pre-dispersion Pre-oxidized carbon black, C13 isopropanol amide, and deionized water were placed in a dispersion vessel and dispersed at high speed until uniform. Then, the dispersion rate was reduced and the temperature was raised to the reaction temperature. Finally, an amino-containing silane coupling agent was added. After the coupling agent reacted completely, a silane coupling agent modified carbon black pre-dispersion was obtained. The mass ratio of the pre-oxidized carbon black, C13 isopropanol amide, deionized water, and amino-containing silane coupling agent is 65:2:1135:1, and other operations are the same as in Example 1. Step 2: Preparation of precursor solution Replace the silica-alumina coated carbon black predispersant with an equal amount of silane coupling agent modified carbon black predispersant, and perform the other operations as in Example 1; Steps 3 and 4 are the same as in Example 1.
[0028] Comparative Example 3: Based on Example 1, step 1, preparing the silica-alumina coated carbon black pre-dispersion, and step 2, preparing the precursor solution, were omitted. Instead, the silica-alumina coated carbon black pre-dispersion was replaced with an equal volume of deionized water. The specific operation is as follows: Step 1, preparing the silica-alumina coated carbon black pre-dispersion, is not performed; Step 2: Preparation of precursor solution Sodium hydroxide, N,N,N-trimethyl-1-adamantyl ammonium hydroxide, and deionized water were mixed evenly, and then aluminum isopropoxide was added. After stirring and mixing evenly, the mixture was placed in an ice-water bath. Tetraethyl silicate was added at a constant temperature of 0°C. After stirring and hydrolysis was complete, the mixture was raised to room temperature, stirred thoroughly, and aged to obtain the precursor solution. The molar ratio of tetraethyl silicate, aluminum isopropoxide, sodium hydroxide, and N,N,N-trimethyl-1-adamantyl ammonium hydroxide is 1:0.06:0.22:0.21. The added deionized water is 6 times the total mass of tetraethyl silicate, aluminum isopropoxide, sodium hydroxide, and N,N,N-trimethyl-1-adamantyl ammonium hydroxide. Other operations are the same as in Example 1; Steps 3 and 4 are the same as in Example 1.
[0029] Comparative Example 4: Based on Example 1, in step 3, preparing the multi-level porous SSZ-13 molecular sieve raw powder, dimethyloctadecyl-(3-trimethoxysilylpropyl)-ammonium chloride was not added. Instead, the amount of dimethyloctadecyl-(3-trimethoxysilylpropyl)-ammonium chloride added was 0.04 times the total molar amount of tetraethyl silicate added to the precursor solution, which was replaced with an equal mass of deionized water. The specific operation is as follows: Steps 1 and 2 are the same as in Example 1; Step 3: Preparation of multi-level porous SSZ-13 molecular sieve raw powder After the precursor solution is evaporated to remove alcohol and pre-crystallized, it is placed in an ice-water bath and slowly added dropwise at 0°C with vigorous stirring. After the addition is complete, vigorous stirring is continued at 0°C until the mixture is homogeneous, and the mixture is then transferred to a hydrothermal reactor. After hydrothermal crystallization, the mixture is centrifuged, washed, dried, and calcined to obtain multi-level porous SSZ-13 molecular sieve raw powder. The amount of deionized water added is 0.04 times the total molar amount of tetraethyl silicate added to the precursor solution, and other operations are the same as in Example 1; Step 4 is the same as in Example 1.
[0030] Testing of carbon dioxide adsorption performance:
[0031] The hierarchical porous molecular sieves obtained in Examples 1-3 and Comparative Examples 1-4 for carbon dioxide adsorption and separation were tested for carbon dioxide adsorption performance according to the following methods: A fixed-bed adsorption breakthrough experimental setup was used for evaluation. This setup consisted of a gas distribution system, a mass flow meter, a constant-temperature adsorption tube, a back pressure valve, and a gas chromatograph (GC). The GC employed a dual-channel detector system combining a thermal conductivity detector (TCD) and a flame ionization detector (FID) for online analysis. The TCD used a TDX-01 column primarily for CO2 analysis. The adsorbent was loaded into the middle of the reactor, and the upper and lower ends of the adsorption bed were filled with 60-80 mesh quartz sand. The adsorbent was activated at 150°C for 6 hours under normal pressure and a flowing 10 wt% H2 / 90 wt% Ar gas stream. The flow rates of all gas streams were regulated and controlled by the mass flow meter. The tail gas was detected online using a gas chromatograph (TCD). The vaporization chamber temperature was 120°C, the detector temperature was 220°C, and the column temperature was 80°C. Reaction conditions: The simulated flue gas composition was 20wt% CO2 and 80wt% N2 to simulate the complex environment of real flue gas; the adsorption temperature was 40℃; and the adsorption pressure was atmospheric pressure. The total gas flow rate was 500 mL / min. The breakthrough point was defined as when the CO2 concentration in the outlet gas stream reached 1wt% of the inlet concentration. The test results are shown in Table 1: Table 1
[0032] As can be seen from the data in Table 1, the hierarchical porous molecular sieves obtained in Examples 1-3 for carbon dioxide adsorption and separation have a breakthrough time greater than 628 s, a dynamic adsorption capacity greater than 2.5 mmol / g, and an apparent diffusion coefficient greater than 5.2 × 10⁻⁶. -12 m 2 / s, append Figure 2The adsorption-desorption curves of Example 1 show that the molecular sieve has a dendritic hierarchical pore structure, indicating that the hierarchical porous molecular sieve obtained in this invention has excellent characteristics such as a dendritic hierarchical pore structure, good pore size distribution, and large carbon dioxide adsorption capacity. In Comparative Example 1, without the addition of C13 isopropanolamide in the step of preparing the silica-alumina coated carbon black pre-dispersion, the breakthrough time and dynamic adsorption capacity of Comparative Example 1 decreased sharply to the lowest values among all examples and comparative examples, and the apparent diffusion coefficient increased significantly. This may be because without the addition of C13 isopropanolamide, it is difficult to uniformly disperse the carbon black. After being coated with silica-alumina, the excessively agglomerated carbon black particles are prone to forming macroporous structures inside the molecular sieve, resulting in a significant increase in the apparent diffusion coefficient. However, these macropores do not help... The improvement in the carbon dioxide adsorption capacity of molecular sieves is macroscopically manifested as a significant decrease in both breakthrough time and dynamic adsorption capacity. In Comparative Example 2, during the preparation of the silicon-aluminum coated carbon black pre-dispersion liquid, the carbon black particles were not coated with silicon-aluminum. The breakthrough time, dynamic adsorption capacity, and apparent diffusion coefficient of Comparative Example 2 all decreased significantly. This may be because the silicon-aluminum coating on the carbon black particle surface can provide silicon and aluminum sources during the crystallization reaction, promoting the in-situ formation of a molecular sieve framework lattice network on the carbon black surface by the active substances in the reaction system. This further promotes the uniformity of carbon black particle dispersion within the molecular sieve body, ultimately resulting in a more uniform distribution of the mesopores formed after the carbon black particles are ablated within the molecular sieve lattice network. Additionally, the reaction... The addition of dimethyloctadecyl-(3-trimethoxysilylpropyl)-ammonium chloride to the system may facilitate the adsorption of silica-alumina coated carbon black particles by its hydrophilic end. This adsorption promotes connectivity between the mesopores formed by the carbon black and the micropores and trace mesopores formed by dimethyloctadecyl-(3-trimethoxysilylpropyl)-ammonium chloride, ultimately promoting the formation of a dendritic hierarchical porous structure. Therefore, silica-alumina coated carbon black can significantly improve the carbon dioxide adsorption performance of hierarchical porous molecular sieves. In Comparative Example 3, without silica-alumina coated carbon black, the breakthrough time, dynamic adsorption capacity, and apparent diffusion coefficient all decreased significantly. This may be because the main function of carbon black particles is to construct mesopores; without carbon black, the number of mesopores in the hierarchical porous molecular sieve ultimately decreases. The amount will decrease significantly, resulting in a sharp decline in carbon dioxide adsorption performance. In Comparative Example 4, without the addition of dimethyloctadecyl-(3-trimethoxysilylpropyl)-ammonium chloride, the breakthrough time, dynamic adsorption capacity, and apparent diffusion coefficient of Comparative Example 4 also decreased significantly. This may be because the role of dimethyloctadecyl-(3-trimethoxysilylpropyl)-ammonium chloride is to construct micropores and a very small number of mesopores inside the molecular sieve. Moreover, the hydrophilic end of dimethyloctadecyl-(3-trimethoxysilylpropyl)-ammonium chloride may more easily adsorb silica-alumina coated carbon black particles, resulting in more interconnected channels between micropores and mesopores in the molecular sieve system. This is the most critical link in improving the carbon dioxide adsorption performance of hierarchical porous molecular sieves.
[0033] Appendix Figure 1The XRD patterns of the hierarchical porous molecular sieves for carbon dioxide adsorption and separation obtained in Examples 1, 3, and 4 are shown below. From bottom to top, they are Comparative Example 4: plate-like hierarchical porous SSZ-13, Comparative Example 3: conventional microporous SSZ-13, and Example 1: dendritic hierarchical porous SSZ-13. They all show typical XRD diffraction peaks of SSZ-13 zeolite, without other impurities, and have good crystallinity. Appendix Figure 2 The figures show the nitrogen adsorption-desorption curves of the hierarchical porous molecular sieves obtained in Examples 1, 3, and 4 for carbon dioxide adsorption and separation. Both the dendritic hierarchical SSZ-13 in Example 1 and the plate-like hierarchical SSZ-13 in Comparative Example 4 exhibit significant hysteresis loops, indicating the presence of a mesoporous structure. Furthermore, the nitrogen adsorption-desorption capacity of the dendritic hierarchical SSZ-13 in Example 1 is significantly greater than that of the plate-like hierarchical SSZ-13 in Comparative Example 4. This demonstrates that the dendritic hierarchical structure, with its interconnected micropores and mesopores, exhibits superior gas adsorption performance. Based on the nitrogen adsorption-desorption curves of Example 1 and the related carbon dioxide adsorption test data, the total pore volume of the hierarchical porous molecular sieve obtained in Example 1 can be calculated to be 0.58 cm³. 3 / g, of which the micropore volume is 0.18 cm³. 3 / g, mesoporous pore volume is 0.40 cm³ 3 / g, with a total specific surface area of 584.57 m². 2 / g.
[0034] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A method for preparing a hierarchical porous molecular sieve for carbon dioxide adsorption and separation, characterized in that: The method for preparing the hierarchical porous molecular sieve for carbon dioxide adsorption and separation includes four steps: preparing a silica-alumina coated carbon black pre-dispersion liquid, preparing a precursor solution, preparing hierarchical porous SSZ-13 molecular sieve raw powder, and ion exchange. The preparation of the silicon-aluminum coated carbon black pre-dispersion involves placing pre-oxidized carbon black, C13 isopropanol amide, and deionized water into a dispersion vessel. After high-speed dispersion to achieve uniformity, the dispersion rate is reduced, and the temperature is raised to the reaction temperature. Then, an amino-containing silane coupling agent is added. After the coupling agent has reacted completely, an aqueous solution of sodium metasilicate is added, followed by the dropwise addition of an aqueous solution of sulfuric acid. The pH value in the vessel is controlled to remain stable between 9 and 10 during the silicon coating reaction. After the silicon coating reaction is completed, an aging process is performed. After aging, high-speed dispersion is performed again. After uniform dispersion, the dispersion rate is reduced, and an aqueous solution of aluminum sulfate is added. Then, an aqueous solution of sodium hydroxide is added dropwise. The pH value in the vessel is controlled to remain stable between 6 and 6.8 during the aluminum coating reaction. After the aluminum coating reaction is completed, a second aging process is performed. After aging, the silicon-aluminum coated carbon black pre-dispersion is obtained. The mass ratio of the pre-oxidized carbon black, C13 isopropanol amide, deionized water, amino-containing silane coupling agent, sodium metasilicate aqueous solution, and aluminum sulfate aqueous solution is (35~100):(1~2.5):(390~1500):(0.1~2):(9~30):(11~40). To prepare the precursor solution, sodium hydroxide, N,N,N-trimethyl-1-adamantyl ammonium hydroxide, and deionized water are mixed evenly, and then silica-alumina coated carbon black pre-dispersion and aluminum isopropoxide are added. After stirring and mixing evenly, the mixture is placed in an ice-water bath, and tetraethyl silicate is added at a constant temperature of 0°C. After stirring and hydrolyzing completely, the mixture is raised to room temperature, stirred thoroughly, and aged to obtain the precursor solution. The molar ratio of tetraethyl silicate, aluminum isopropoxide, sodium hydroxide, and N,N,N-trimethyl-1-adamantyl ammonium hydroxide is as follows: SiO2 : Al2O3 : Na2O : N,N,N-trimethyl-1-adamantyl ammonium hydroxide = 1 : (0.09~0.1) : (0.2~0.24) : (0.2~0.23). The mass of the silica-alumina coated carbon black pre-dispersion is 1 to 10 times the total mass of tetraethyl silicate, aluminum isopropoxide, sodium hydroxide, and N,N,N-trimethyl-1-adamantyl ammonium hydroxide. To prepare the multi-level porous SSZ-13 molecular sieve raw powder, the precursor solution is evaporated to remove alcohol and pre-crystallized, then placed in an ice-water bath at 0°C with vigorous stirring. Dimethyloctadecyl-(3-trimethoxysilylpropyl)-ammonium chloride is slowly added dropwise. After the addition is complete, vigorous stirring at 0°C continues until the mixture is homogeneous, resulting in a mixed solution. The mixed solution is then transferred to a hydrothermal reactor. After hydrothermal crystallization, the raw powder is obtained by centrifugation, washing, drying, and calcination.
2. The method for preparing a hierarchical porous molecular sieve for carbon dioxide adsorption and separation according to claim 1, characterized in that: The pre-oxidation treatment involves mixing carbon black with an ammonium persulfate aqueous solution with a mass concentration of 0.5 wt‰ at a mass ratio of 9:100, stirring and oxidizing at room temperature for 24 hours, and then filtering and drying at 100°C for 12 hours to obtain the pre-oxidized carbon black. The particle size of the carbon black is 9~20nm; The amino-containing silane coupling agent is at least one of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, and N-(2-aminoethyl)-3-aminopropyltriethoxysilane.
3. The method for preparing a hierarchical porous molecular sieve for carbon dioxide adsorption and separation according to claim 1, characterized in that: The sodium metasilicate aqueous solution contains 8-13 wt% sodium metasilicate. The sulfuric acid aqueous solution contains 6-10 wt% sulfuric acid. The aluminum sulfate aqueous solution contains 10-20 wt% aluminum sulfate. The sodium hydroxide aqueous solution contains 4-10 wt% sodium hydroxide.
4. The method for preparing a hierarchical porous molecular sieve for carbon dioxide adsorption and separation according to claim 1, characterized in that: The added deionized water is 1 to 13 times the total mass of tetraethyl silicate, aluminum isopropoxide, sodium hydroxide, and N,N,N-trimethyl-1-adamantyl ammonium hydroxide.
5. The method for preparing a hierarchical porous molecular sieve for carbon dioxide adsorption and separation according to claim 1, characterized in that: The amount of dimethyloctadecyl-(3-trimethoxysilylpropyl)-ammonium chloride added is 0.03 to 0.05 times the total molar amount of tetraethyl silicate added to the precursor solution; The specific operation of the evaporation to remove alcohol is as follows: the precursor solution is transferred into a rotary evaporator and continuously evaporated for 4 to 10 hours under the conditions of temperature 40 to 80°C, rotation speed 50 to 100 rpm and vacuum degree 50 to 80 kPa. The pre-crystallization temperature is 90~120℃, and the pre-crystallization time is 10~20 hours; The vigorous stirring is carried out at a speed of 1500~3500 rpm; The dimethyloctadecyl-(3-trimethoxysilylpropyl)-ammonium chloride is added dropwise at a rate of 10-120 g / min. The mixture is stirred vigorously until homogeneous, and the stirring and mixing time is 4 to 8 hours. The hydrothermal crystallization is carried out at a temperature of 120~180℃ for 3~10 days. The calcination is carried out in an argon or nitrogen atmosphere at 350-400°C for 4-7 hours, followed by calcination in air at 530-580°C for 4-6 hours.
6. The method for preparing a hierarchical porous molecular sieve for carbon dioxide adsorption and separation according to claim 1, characterized in that: The ion exchange process involves adding the raw powder of hierarchical SSZ-13 molecular sieve to an ammonium chloride aqueous solution and performing a first ion exchange under constant temperature stirring. After filtration, washing, and drying, a second ion exchange is performed using the same constant temperature stirring operation. Then, after filtration, washing, and drying, a third ion exchange is performed under the same constant temperature stirring operation. Finally, the filtered, washed, and dried powder is calcined at 530~580°C for 4~6 hours to obtain a hierarchical porous molecular sieve for carbon dioxide adsorption and separation.
7. The method for preparing a hierarchical porous molecular sieve for carbon dioxide adsorption and separation according to claim 6, characterized in that: The concentration of the ammonium chloride aqueous solution is 0.8~1 mol / L; In the first, second, and third ion exchanges, the mass ratio of solid powder to ammonium chloride aqueous solution is 1:1 to 3.5 in each ion exchange.
8. A multi-level porous molecular sieve for carbon dioxide adsorption and separation prepared by the preparation method according to any one of claims 1-7.
Citation Information
Patent Citations
Preparation method and application of hierarchical pore SSZ-13 molecular sieve and method for preparing olefin from methanol
CN112978749A
Preparation method of SSZ-13 molecular sieve with hierarchical porous structure as well as obtained product and application of SSZ-13 molecular sieve
CN114835133A
Hierarchical porous SSZ-13 molecular sieve catalyst, method for synthesizing same and application of hierarchical porous SSZ-13 molecular sieve catalyst
CN106830007A
Metal organic framework nanosheet and method for producing same
US20190247825A1